The Role of Public-Third Sector Relationships in Solving Social Issues: the Case of One-Stop-Shop Service for the Promotion of Female Immigrant Entrepreneurship in Montreal - Sylvie Paré; Ralph Christian Maloumby-Baka (Entrepreneurial Business and Economics Review, 2015)
Objective: The objective of this paper is to review the most relevant literature on the relationship between the State and the third sector in the development of responses to important social issues. This exploratory paper specifically examines a case of public third sector relationships, Montreal CEMFII, within the most consolidated relation types to highlight what characteristics match with it and what do not match. Research Design & Methods: An extensive review of the literature on the relationship between the State and the third sector was performed in order to develop a model of such relationships and stress their principal characteristics. A conceptual effort was made to situate the CEMFII within the more consolidated relation forms, in order to provide evidence of their pros and cons in such specific case. Findings: It is suggested that the development of a One-Stop-Shop service could remedy some of the difficulties female immigrants face when attempting to develop businesses. The paper also argues that the CEMFII, as a product of the State - third sector interactions, has been risky and complicated. However, while there is no evidence that its public funds dependency constitutes a threat to the mission and autonomy of the not-for-profit organisations involved, there exists a sustainability issue linked to political leadership changes. Implications & Recommendations: While the effectiveness of the CEMFII to solve female immigrant entrepreneurs difficulties, which should be furthermore ascertained with data in a future research, is generally acknowledged, it might be useful that the third sector organisations acquire a financial autonomy to diminish their dependency on the public funds, which is subject to political leadership changes, and to guarantee the sustainability of the project. Contribution & Value Added: The uniqueness of this work lies in applying general frameworks of public- third sector relations to a specific case within a specific urban socioeconomic context, where the effects of political leadership changes can be clearly viewed.